Mitos dalam Cerita Rakyat Purbalingga: Myths on Purbalingga Folklore - Ery Agus Kurnianto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
In social life, we cannot deny that myths are still something that is believed to be true and have sacred values. Aspects of human life cannot separate from the myths which are created, developed, and believed to be true by humans as individuals and as social groups. This study examines the type of myths and describes the benefits of myths on Purbalingga folklore. This explanatory because it is explaining the meanings contained in oral traditions; words meaning, language meaning and symbol meaning. To analyze the data, the researcher uses a library research. The method for this research is a descriptive comparative analysis. The approach for this research is a discursive approach. The results of the study show that the myths found in Purbalingga folklore are (1) myths of saints and magic, (2) sacred myth, (3) myths of the origin of the place,and (4) myths of the magical beasts. The results of the analysis that mythical Purbalingga community has a function (1) maintain social order. (2) maintain social status.